2017
DOI: 10.1021/acs.jmedchem.6b01816
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Small-Molecule Degrader of Bromodomain and Extra-Terminal (BET) Proteins with Picomolar Cellular Potencies and Capable of Achieving Tumor Regression

Abstract: The bromodomain and extra-terminal (BET) family proteins, consisting of BRD2, BRD3, BRD4, and testis-specific BRDT members, are epigenetic “readers” and play a key role in the regulation of gene transcription. BET proteins are considered to be attractive therapeutic targets for cancer and other human diseases. Recently, heterobifunctional small-molecule BET degraders have been designed based upon the proteolysis targeting chimera (PROTAC) concept to induce BET protein degradation. Herein, we present our design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
294
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(308 citation statements)
references
References 30 publications
14
294
0
Order By: Relevance
“…Superior efficacy compared to BET inhibition was also observed for a pomalidomide based PROTAC comprising a second generation BET inhibitor which induces growth inhibition and apoptosis in triple-negative breast cancers (TNBC) (Bai et al, 2017). Tethering this second generation BET inhibitor to lenalidomide resulted in PROTACs degrading BET proteins at picomolar concentration which caused >90% tumor regression in acute leukemia mouse xenograft models (Zhou et al, 2017). These studies highlight the therapeutic advantage of event -driven pharmacology given that BRD4 inhibition is often counteracted by compensatory BRD4 overexpression to hamper inhibitor efficacy (Shimamura et al, 2013).…”
Section: Targeted Proteasomal Degradationmentioning
confidence: 99%
“…Superior efficacy compared to BET inhibition was also observed for a pomalidomide based PROTAC comprising a second generation BET inhibitor which induces growth inhibition and apoptosis in triple-negative breast cancers (TNBC) (Bai et al, 2017). Tethering this second generation BET inhibitor to lenalidomide resulted in PROTACs degrading BET proteins at picomolar concentration which caused >90% tumor regression in acute leukemia mouse xenograft models (Zhou et al, 2017). These studies highlight the therapeutic advantage of event -driven pharmacology given that BRD4 inhibition is often counteracted by compensatory BRD4 overexpression to hamper inhibitor efficacy (Shimamura et al, 2013).…”
Section: Targeted Proteasomal Degradationmentioning
confidence: 99%
“…Molecules which bind to an E3 ubiquitin ligase are also of great interest to the field of targeted protein degradation, particularly as recruiting elements for proteolysis targeting chimera (PROTACs) . Indeed, IMiDs have been widely used as E3 recruiting elements to enable the degradation of a wide variety of targets …”
Section: Figurementioning
confidence: 99%
“…Furthermore, studies with BET degraders demonstrated potent inhibition of cancer cell growth and the induction of apoptosis when compared to the corresponding BET inhibitors. 24, 25, 27, 38 …”
mentioning
confidence: 99%